The Challenges of Building the Model of the Modern State in Iraq after 2011 through a Tripartite: Rent - Identity and Equality - Zerrouga, Ismail (Journal of Legal Studies and Researches, 2021)
The follower of the modern state-building process in Iraq after the US withdrawal in 2011, notes that it is still unable to get out of the circle of rentier economy, which aims to try to quickly reach the welfare state, and thus move to a society based on the values ​​of citizenship, rights and fredooms, The Iraqi rentier economy hindered the normal development of society, and hindered the establishment of a society that reproduces itself as a strong contractual society of individuals able to impose their logic of contracting independently of the state, Hence their loyalty has declined The Iraqi state, in return for growing loyalty to outside parties, believes that it supports it in strengthening its identity, Which is what this study is trying to discuss